Measure for measure - Crewe, Jonathan . (New York : Penguin Books, 2000)
An annotated edition of Shakespeare's tragicomedy in which an unjust Viennese deputy offers to lift a death sentence from a young woman's brother in return for sexual favors from her; also includes essays on Shakespeare's theatrical world and his texts, and a scholarly introduction.
Keywords: Measure for measure; Chastity -- Drama